Realizing the soft infrastructure mixing of Shanghai's catering industry based on land expansion and population growth - Zhenchao Zhang; Andong Guo; Chuang Tian (Heliyon, 2024)
This study takes Shanghai's restaurants as a case study of urban soft infrastructure, employing big data sets from third-party website platforms for multi-source data fusion, to deeply analyze the impact of urban land expansion and population dynamics on the availability, affordability, acceptability, and accessibility of restaurants. The case study reveals that, despite the Shanghai municipal authorities' focus on mitigating overcrowding in the central urban areas, soft infrastructure such as restaurants in new urban districts remains at a relative disadvantage. The decentralization of soft infrastructure to peripheral urban areas has not met policy expectations, presenting a spatial imbalance characterized by greater provision in the main urban areas than in new urban districts, and higher in Puxi than in Pudong. The single-threshold model uncovers that the positive impact of land urbanization and population dynamics on restaurant convenience undergoes a transformation after reaching a certain critical point, where the linear relationship and synchronous growth shift. By controlling the development area of construction land and the population density within regions, a dynamic combination of availability, affordability, acceptability, and accessibility of restaurants can be achieved. This forms a spatio-temporal management strategy that integrates land, population, and comfort facilities, potentially alleviating the inequity of comfort facilities in Shanghai and the central urban areas' siphoning effect.